Occupational Health and Safety Risk Analysis in High-Rise Urban Building Construction Projects - Sitohang, Tua; Sembiring, Desiran; Murtiadi, Suryawan (ASTONJADRO, 2026)
Occupational Safety and Health (OHS) is a crucial aspect in the implementation of construction projects, especially in the construction of high-rise buildings in urban areas that have a high level of complexity and risk. Unmanaged OHS risks can cause work accidents, project delays, and significant financial losses. This study aims to create solution steps by analyzing OHS risks and knowing the factors that cause an increase in OHS risks in buildings at the Ministry of Finance State Flats, Jl. Kemanggisan, Palmerah District, West Jakarta, Jakarta. The research method used is a qualitative and quantitative approach with data collection techniques through questionnaire surveys, interviews with related parties (contractors, supervisors, and workers), and field observations. Risk analysis was carried out using the HIRARC (Hazard Identification, Risk Assessment and Risk Control) method, which categorizes risk levels based on probability and impact. The identification results show that each sector faces varying OHS risks, ranging from moderate, high to extreme categories, especially in work at heights, use of heavy equipment, exposure to chemicals, and electrical risks. These findings emphasize the importance of implementing a structured OSH system, including mitigation planning, routine supervision, safety training, and work area management. An effective OSH strategy is expected to improve workplace safety, reduce accidents, and support the smooth running and overall success of the project.